2018
DOI: 10.1002/oby.22200
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Weight‐Loss Methods and Weight Change: Ten‐Year Analysis in the Swedish Obese Subjects Study Control Group

Abstract: Over 10 years, the majority of the participants of the SOS control group reported continuous efforts to lose weight. These results illustrate the constant struggle individuals with severe obesity are facing and that, on average, the results of long-term weight loss and weight maintenance were discouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…This is particularly important because of the high prevalence of previous weight loss attempts among persons with obesity, the lack of standardized weight control methods offered by the health care system, and the discouraging long-term results of weight loss attempts. 23,24,28 In the current study, it was not specified whether the support required for weight loss meant support from the health care provider or, for example, from family, friends or others, but because of the high prevalence of various types of health problems, it seems reasonable that the support should be provided by the health care system. Multiple barriers to weight loss, such as high BMI, more health conditions, and low confidence among patients with obesity, have also been reported from a study conducted in primary care in the United Kingdom.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is particularly important because of the high prevalence of previous weight loss attempts among persons with obesity, the lack of standardized weight control methods offered by the health care system, and the discouraging long-term results of weight loss attempts. 23,24,28 In the current study, it was not specified whether the support required for weight loss meant support from the health care provider or, for example, from family, friends or others, but because of the high prevalence of various types of health problems, it seems reasonable that the support should be provided by the health care system. Multiple barriers to weight loss, such as high BMI, more health conditions, and low confidence among patients with obesity, have also been reported from a study conducted in primary care in the United Kingdom.…”
Section: Discussionmentioning
confidence: 98%
“…However, an English study found that weight loss attempts were only modestly related to health conditions . Although trying to lose weight is very common among people with obesity, the long‐term results are discouraging . More knowledge is thus needed about the health status, contacts with health care, and other health‐related factors among those who want to lose weight and do not/do need weight loss support.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects from the surgery group underwent bariatric surgery at baseline (19% gastric banding, 68% vertical banded gastroplasty and 13% gastric bypass). The control group received conventional non-surgical obesity treatment at their centres of registration (ranging from intensive lifestyle modifications to no treatment of any kind) and no attempt was made to standardize the non-surgical treatment [ 22 ]. All the subjects gave their written or oral informed consent to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects from the bariatric surgery group underwent vertical banded gastroplasty (68%), gastric banding (19%), or gastric bypass (13%). The control group received conventional non-surgical treatment for obesity at their centres of registration, which ranged from intensive lifestyle modifications to no treatment, with no attempt to standardize the non-surgical treatment (31).…”
Section: Sos Study Designmentioning
confidence: 99%